Microbes in land use change management - Singh, Jay Shankar (Elsevier, 2021)
"Microbes in Land Use Change Management details the various roles of microbial resources in management of land uses and how the microbes can be used for the source of income due to their cultivation for the purpose of biomass and bioenergy production. Using various techniques, the disturbed and marginal lands may also be restored eco-friendly in present era to fulfil the feeding needs of mankind around the globe. Microbes in Land Use Change Management provides standard and up to date information towards the land use change management using various microbial technologies to enhance the productivity of agriculture. Needless to say that Microbes in Land Use Change Management also considers the areas including generation of alternative energy sources, restoration of degraded and marginal lands, mitigation of global warming gases and next generation -omics technique etc. Land use change affects environment conditions and soil microbial community. Microbial population and its species diversity have influence in maintaining ecosystem balance. The study of changes of microbial population provides an idea about the variation occurring in a specific area and possibilities of restoration. Meant for a multidisciplinary audience Microbes in Land Use Change Management shows the need of next-generation omics technologies to explore microbial diversity."--